Calling in the heat: the zebra finch incubation call depends on heat AND reproductive stage—a comment on McDiarmid et al. 2018. (22nd April 2019) - Mariette, Mylene M; Buchanan, Katherine L
Abstract : We reanalysed McDiarmid et al data and showed that, contrary to their title, "calling in the heat" increases considerably in late incubation. This dataset independently confirms our previous findings, which raises interesting questions concerning the evolution of this signal of heat stress to embryos.